1987
DOI: 10.1038/bjc.1987.204
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and prognosis in human breast cancer

Abstract: Prostaglandins E2 and F2 alpha (PGE2 and PGF2 alpha) were measured by gas liquid chromatography--mass spectrometry (glc-ms) in extracts of primary tumours from 78 patients with early breast cancer. These levels have been related to factors of established prognostic value and the patients disease-free interval. Although there was a wide variation in amounts of both prostaglandins extracted from different tumours, no significant relationship was observed between levels of prostaglandins and oestrogen receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Vergote et al (1985) found that a good prognosis was associated with a high yield of tumour PGF2a,, but the biological effects of this PG are often different, and sometimes opposite, to those of PGE2. In contrast, Watson et al (1987) found no relationship of PGE2 and PGF2a to the disease-free interval. Survival When 25 patients had died and the follow-up time was 1.5-54 months, we reported an inverse correlation between total PG-LM and the time to death .…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…Vergote et al (1985) found that a good prognosis was associated with a high yield of tumour PGF2a,, but the biological effects of this PG are often different, and sometimes opposite, to those of PGE2. In contrast, Watson et al (1987) found no relationship of PGE2 and PGF2a to the disease-free interval. Survival When 25 patients had died and the follow-up time was 1.5-54 months, we reported an inverse correlation between total PG-LM and the time to death .…”
Section: Resultscontrasting
confidence: 40%
“…In contrast, Karmali et al (1983) and Watson et al (1987) found no relationship between PGs and tumour size. Our inverse correlation with PG-LM was due mainly to the results with only the small and medium tumours.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Although initial studies suggested a poor prognosis in patients with high PG levels (Bennett et al, 1977) others have shown either no relationship to established prognostic indices (Wilson et al, 1980;Watson et al, 1987) or a correlation with favourable prognostic factors (Karmali et al, 1983;Watson and Chuah, 1985;Fulton et al, 1982). These disparate findings could be attributed to various factors including: differences in the techniques employed; substrate availability; and tissue handling as well as the labile nature of both tissue PGE2 levels per se and the rapid turnover of the enzymes regulating PGE2 production and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Data regard ing the prognostic value of tumour prosta noid levels are highly controversial. Al though Bennett et al [16] and Rolland et al [ 13] initially found that an increased produc tion of prostaglandin-like material and PGE2 might be used as marker of a high metastatic potential of a breast tumour, other authors showed that there was no correlation be tween tumour prostaglandin levels and prog nosis [17,18], In a later analysis, Bennett et al [19] reported that disease-free survival was longest with an intermediate production of total prostaglandin-like-material by the tumour.…”
Section: Discussionmentioning
confidence: 99%